Exploiting the capacity of Labrys Portucalensis strain F11 for biotransformation of fluoroaromatic compounds - Moreira, Irina Susana Sousa (2012)
Environmental contamination with toxic chemicals of human origin is a threat to ecosystems and public health. Thus, it is extremely important to understand and explore the removal of these contaminants from different environments through biodegradation. The main objective of the work described in this thesis was the exploitation of the potential of Labrys portucalensis F11 – a bacterial strain previously isolated by its ability to degrade fluorobenzene (FB) - for biotransformation of fluorinated aromatic compounds of different complexity. Typically, contaminated environments are not contaminated with a single pollutant but with mixtures of pollutants. In particular the presence of organic compounds and metals in the same ecosystem, or appearing simultaneously in wastewater streams, is very common. In this study, the effect of three metals with different biological importance - iron, copper and silver - on the degradation of FB by strain F11 was evaluated. At a concentration of 1 mM, iron proved to be beneficial for bacterial growth without adversely affecting the biodegradation of up to 2 mM of FB. The presence of 1 mM of copper and silver inhibited the degradation of FB and led to the accumulation of intermediate metabolites, catechol and 4-fluorocatecol suggesting inhibition of the catechol 1,2-dioxygenase, which is a key enzyme of the metabolic pathway of FB. The degradation of compounds with chemical structures similar to FB, namely chlorobenzene (CB) and difluorobenzenes (DFBS), by L. portucalensis was investigated. Strain F11 was able to cometabolise CB in the presence of FB or when previously induced by this compound. Total degradation of 0.5 mM of each substrate was observed when both were added to the culture medium. Strain F11 was capable of degrading CB when the expression of enzymes is induced by FB however CB was not able to induce the enzymes for its own degradation. For DFBS, strain F11 proved to be able to degrade 0.5 mM of 1,3-DFB as sole carbon source, and to degrade 1,4-DFB (0.5 mM) in cometabolism with FB (0.5 mM). Strain F11 was unable to degrade 1,2-DFB and this compound inhibited the degradation of FB. These results reinforce the importance of the nature, number and position of the substituents in the molecule for enzyme expression and subsequently conversion of the target compounds. Fluoxetine (FLX) is a fluorinated chiral drug, which contamination, toxicity and persistence in the environment have been well documented in the past years. L. portucalensis F11 showed to be able to degrade both enantiomers of this compound as the sole carbon source (up to 9 μM) and in the presence of a conventional carbon source, sodium acetate (up to 89 μM of FLX). Degradation extents of at least 80% of total FLX were obtained. At the lowest FLX concentration tested (2 μM) as single carbon source, degradation was complete and fluoride release was stoichiometric. The degradation was shown to be enantioselective, with preferential degradation of R-FLX in relation to S-FLX. The transient formation of norfluoxetine (NFLX) as an intermediary metabolite was detected. With the objective of finding the genes responsible for the expression of FB dioxygenase, a genomic library consisting of 960 clones was constructed from the DNA of L. portucalensis F11. This library can be used for future work, such as the generation and confirmation of sequencing data, for comparative genomic studies or to search for other genes of interest. It is important to note that this strain has shown extraordinary capabilities of degradation of toxic compounds, and as such it would be very interesting to further study the genes that confer these capabilities. A partial nucleotide sequence of the gene cluster involved in FB degradation was determined. Sequencing results revealed the presence of four open reading frames, namely the gene coding for 1,2-catechol dioxygenase, and three genes encoding a ringhydroxylating dioxygenase (alpha and beta subunit of the dioxygenase component and the oxidoreductase component). Alignment of the deduced aminoacid sequences with sequences of others ring-hydoxylating dioxygenases revealed a high degree of similarity (≥80% identity) to the components of (halo)benzoate dioxygenases. The conserved amino acid residues that are involved in cofactor binding were also identified in the protein sequence. Recombinant strains carrying the putative FB dioxygenase genes were tested for expression. The SDS-PAGE analysis revealed that most of the expressed protein was on the pellet fraction and not on the soluble form, which could be due to improper folding of the enzyme components. Decrease of substrate concentration was observed in bioconversion experiments but the product formed was not detected/ identify. Overall, strain F11 revealed to be capable of degrading a vast range of fluorinated compounds with different complexity and as such can be a potential strain to devise biotechnological solutions for biotransformation processes.